Valorisation des sous-produits de l'oasis pour la gestion durable des ressources naturelles et la chaîne de valeur des aliments des petits ruminants - Moujahed, Nizar; Mannai, Amal (National Agronomic Institute of Tunisia, 2023)
The report summarizes a two-day workshop in Kebili, focusing on the development and optimization of local feed resources, specifically date palm by-products. It highlights the potential for growth in utilizing these by-products and underscores the need to address knowledge gaps for sustainable agricultural practices in the region.